Initial experience with pre-activation of the cardiac catheterization lab and emergency room bypass for patients with ST-elevation myocardial infarction in Halifax, Nova Scotia. (1st November 2016) - Bata, Adil; Quraishi, Ata ur Rehman; Love, Michael; Title, Lawrence; Beydoun, Hussein; Lee, Tony; Nadeem, Najaf; Kidwai, Bakhtiar; Kells, Catherine; Curran, Helen
Abstract: Background: To determine whether pre-activation of the cardiac catheterization lab by Emergency Health Services (EHS) with a single call system in the field was associated with reduced time to reperfusion in patients with ST-Elevation Myocardial Infarction (STEMI) undergoing primary percutaneous coronary intervention (PPCI). Methods: Consecutive STEMI patients identified by EHS and subsequently taken to the Queen Elizabeth II Health Sciences Center (QEIIHSC) for PPCI between February 1, 2011 and January 30, 2013 were examined. Patients who had pre-activation of the catheterization lab from the field (pre-act group) after the acquisition of the LifeNet® system (Physio Control, Redmond Washington) were compared to those who had usual activation (routine group) prior to the acquisition of the LifeNet® system, for outcomes including treatment timeline data and mortality. Results: 271 patients were included in the analysis, 149 patients in the pre-act group and 122 patients in the routine group. Door-to-device (DTD) times of less than 90 min were achieved more frequently in the Pre-act group (91.9% vs. 62.2%; P < 0.001). DTD time was shorter in the Pre-act group (48 min IQR: 38 to 63 min vs. 78 min IQR: 64–101 min; p = 0.001) as was first medical contact-to-device (FMCTD) time (91 min IQR: 78 to 106 min vs. 115 min IQR: 90 to 139 min; P < 0.001). False activation of the catheterization lab was infrequent (1.3%). Conclusions: Implementation of catheterization lab pre-activation using the LifeNet® system was associated with more efficient reperfusion times as measured by reduced FMCTD and DTD times without excess false activation rates.